1998
DOI: 10.1093/ejo/20.5.517
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of acceptance of different types of functional appliances

Abstract: Patients' acceptance of an orthodontic appliance may influence compliance and thus contribute to a successful outcome of treatment. The aim of this study was to assess the influence of shape and design of different types of functional appliances on their acceptance by patients. For each of 10 adult volunteer subjects employed in the study eight different functional appliances were fabricated which had a varying extension of the resin base and amount of interocclusal opening. Effects of appliances on speech, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 8 publications
4
30
2
7
Order By: Relevance
“…Esta também possibilita o diagnóstico diferencial entre apnéia obstrutiva e central, uma vez que os aparelhos são mais bem indicados nos casos de apnéia obstrutiva leve e moderada 33 , com IAH até 30, em pacientes retrognatas, não muito acima do peso, e como coadjuvante em outros tratamentos ou quando estes não mostram bons resultados 8 . Para a determinação do tipo de aparelho a ser adotado neste experimento, levou-se em consideração o estudo de Sergi e Zentner 27 , onde foi demonstrado que o Bionator foi o dispositivo melhor aceito pelos pacientes. Além disso, suas características se adequam ao mecanismo de ação que os aparelhos intrabucais devem apresentar para o tratamento da SAOS.…”
Section: Discussionunclassified
“…Esta também possibilita o diagnóstico diferencial entre apnéia obstrutiva e central, uma vez que os aparelhos são mais bem indicados nos casos de apnéia obstrutiva leve e moderada 33 , com IAH até 30, em pacientes retrognatas, não muito acima do peso, e como coadjuvante em outros tratamentos ou quando estes não mostram bons resultados 8 . Para a determinação do tipo de aparelho a ser adotado neste experimento, levou-se em consideração o estudo de Sergi e Zentner 27 , onde foi demonstrado que o Bionator foi o dispositivo melhor aceito pelos pacientes. Além disso, suas características se adequam ao mecanismo de ação que os aparelhos intrabucais devem apresentar para o tratamento da SAOS.…”
Section: Discussionunclassified
“…3 The effect of appliances on taste perceptions has always been a controversial subject. 4 Several investigators have indicated a loss of taste sensation associated with palatal coverage. 4 Others have found that appliance either exerted no effect on taste perception or actually enhanced this perception.…”
Section: 5005/jp-journals-10024-2093mentioning
confidence: 99%
“…4 Several investigators have indicated a loss of taste sensation associated with palatal coverage. 4 Others have found that appliance either exerted no effect on taste perception or actually enhanced this perception. 4 Clinical experience suggests that upper removable or removable prosthetic appliance might affect taste and smell by disturbing the natural airflow between the oral and nasal cavities.…”
Section: 5005/jp-journals-10024-2093mentioning
confidence: 99%
See 2 more Smart Citations